Historyczne przesłanki kształtowania się polskiej kultury organizacyjnej oraz jej współczesne manifestacje w postawach i doznaniach psychicznych - Hryniewicz, Janusz T. (Człowiek i Społeczeństwo, 2014)
The aims of the paper are: 1. Description (of the place) of Poland in the context of the economic and cultural divisions of the European space. 2. Checking if the hitherto divisions of European space are still important. In this context, the cultural division of European space is analyzed in cross – Catholic and Protestant – cultural circles. Economic division was initiated in the XVI century and divided Europe into two parts. In the first of them (Western Europe) capitalism was initialized. In the second the East European economic system has emerged. This economic system was based on agriculture and its key institution was the manor farm. The Polish organizational culture is an effect of participation in: the Catholic cultural circle and East European economic system. Contemporary researches show that the manor farm tradition is still in existence in the attitudes of workers and managers alike.